Perlawanan Perempuan dalam Novel Sunda Sandekala Karya Godi Suwarna - Maryanti, Sri; Rahayu, Lina Meilinawati; Aksa, Yati (JURNAL PESONA, 2017)
AbstractÂ Female figures position in a Sundanese novel entitled Sandekala is in accordance with the concept of docile bodies which is stated by Michael. In general, the novel tends to present obedient women. The female figures are disclosed passively and gagged with the result that oppression undergone is blurred due to less resistance. Some argument prompt this research, particularly in relation to women issue. The other supporting issue is concerned with women represented in Sundanese social condition and Sundanese women attitude who is willing to discharge from being inferior. The most interesting of the novel is when the main character named Dewi, is accentuated. She is depicted as a college student and an activist who struggles similarly as men do. The presence of Dewi is peculiar in the novel. Since she is portrayed differently from other female characters. The novel exposes the character of Dewi as a symbol of women resistance.Key words:Â  female, oppression, resistance